Eduction of equilibrium state in vodkas by means of 1H NMR spectroscopy - Kuzmin, Oleg; Topol’nik, Vera; Mironchuk, Valeriy (My University, 2014)
Eduction of equilibrium state of hydroxyl proton of ethanol and water in various samples of vodkas and flavored vodkas produced in Ukraine, using 1H NMR-spectroscopy.
Keywords: 1H ЯМР спектроскопія; 1H NMR spectroscopy; водно-спиртова суміш; водно-спиртовая смесь; aqueous-alcoholic mixture; горілка; водка; vodka; кафедра технології ресторанної і аюрведичної продукції; кафедра технологічного обладнання та комп’ютерних технологій проектування